Pergeseran Pola Keberagamaan Masyarakat di Kampung Inggris Pare Pasca Terjadinya Perubahan Struktur Sosialnya - Suko Susilo (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2023)
This article discusses the shift in religious patterns that occurred in the Muslim community of Kampung Inggris Pare. Kampung Inggris Pare is located in the Pare Sub-district, Kediri District, East Java, Indonesia, and is known as an English language education center that is visited by people from various regions. Initially, the Muslim community in the English Village Pare had a strong religious pattern and was closely related to Islamic traditions. They regularly follow religious practices, such as praying, fasting, and attending knowledge assemblies. In addition, they have established close social ties with local scholars and religious leaders. However, in recent years, there has been a shift in religious patterns among the Muslim community in the Kampung Inggris Pare. This study aims to analyze the factors that influence the shift in Islamic religious patterns in the community of Kampung Inggris Pare. To achieve this goal, the researcher used a qualitative approach that involved several research methods, including in-depth interviews, participant observation, and document analysis. This qualitative approach allows researchers to gain a deeper understanding of the changes that occur and the dynamics behind this shift in religious patterns. This research found that the rapid development of English language education and foreign culture has had a significant impact on the pattern of religiosity. People have begun to experience changes in their religious priorities and focuses. Economic development and increased social mobility also played important roles in this change. People who were previously more focused on religious education and activities are now more oriented towards finding better jobs and economic opportunities. Religious priorities tend to shift towards material success and modern lifestyles. This shift in religious patterns not only affects religious practices but also the social structure and values upheld by the Muslim community in Kampung Inggris Pare.